Eksistensi Jaminan Dalam Penangguhan Penahanan Seorang Tersangka Atau Terdakwa - Putu Arya Adi Sastra; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Fakultas Hukum Universitas Warmadewa, 2024)
The regulation of suspension of detention has several procedures and considerations listed in Article 31 of the Criminal Procedure Code as well as Article 35 and Article 36 of Government Regulation No. 27 of 1983 concerning the Implementation of the Criminal Procedure Code and Decree of the Minister of Justice of the Republic of Indonesia No. M.14.PW.07.03 of 1983, but these regulations cannot provide a comprehensive description of the procedures or procedures for suspending the detention of a suspect or defendant. In addition, the subjective assessment of the apparatus authorized to grant suspension of detention is also very broad in scope so that it is vulnerable to misinterpretation by authorized law enforcement officers. So the suggestions that can be given are the need to make laws or implementing regulations that are clearer and more detailed in regulating the procedures for implementing suspension of detention and in the context of law enforcement that embodies justice, the apparatus authorized to grant suspension of detention of a suspect or defendant should provide more careful consideration and be accountable to the public in approving the request for suspension of a suspect or defendant. Considering that the authority given to the apparatus by the law is a subjective authority that is vulnerable to misuse.